2003
DOI: 10.1177/10598405030190030701
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of School Nursing on School Performance: A Research Synthesis

Abstract: School nurses work in an educational setting. Due to budget cuts, different goals, and confusion between educators and nurses regarding the school nurse role, school nurses are being asked to demonstrate their effectiveness and justify their presence in elementary and secondary schools. Although school nursing was first initiated 100 years ago, a review of the literature published since 1965 indicates that 15 studies have been conducted that examine the impact of school nurses on academic performance. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 31 publications
(144 reference statements)
2
62
0
Order By: Relevance
“…It is suggested that this negative correlation is stronger in schools where nurse-student rate is lower, and the school nurse works full-time, and that nursing interventions aimed at students with high absenteeism help reduce absenteeism rates. 12,15,16,26,27 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that this negative correlation is stronger in schools where nurse-student rate is lower, and the school nurse works full-time, and that nursing interventions aimed at students with high absenteeism help reduce absenteeism rates. 12,15,16,26,27 …”
Section: Discussionmentioning
confidence: 99%
“…Leaving school early due to injury or sickness becomes a less common phenomenon when students are able to see a nurse at school. 12,15-17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Examples of studies supporting this conclusion have demonstrated that a school nurse can influence a student's school performance, absenteeism, and overall quality of life. 5-7 …”
Section: Literature Reviewmentioning
confidence: 99%
“…In caring for CCC in the school setting, school nurses promote normal development, health, and safety. 26,27 Schools provide a stable environment for children, and since children spend a great deal of time there, the school is positioned as a place where health care often needs to be delivered. Currently, there are about 77 000 school nurses in the United States, caring for 53 million students.…”
Section: School Nurse Rolementioning
confidence: 99%